OPTIMIZATION DIADICAL RELATIONS AND INTERACTIONS IN THE SYSTEM "TEACHER-STUDENT" - Tanita Lyurina (Vasyl Stefanyk Precarpathian National University, 2015)
In the article there are presented the pedagogical terms of optimization of interpersonal relations of interactive co-operation in the system "teacher - student" during individual musical lessons in the process of preparation of future teachers to a development of creative potential of students.